Implementasi Supervisi Akademik pada MAN Insan Cendekia Provinsi Jambi - Mohamad Muspawi (Pusat Penerbitan Universitas (P2U) Unisba, 2017)
Abstract This study aims to determine the condition of implementation of academic supervision at MAN Insan Cendekia Jambi province. Where the manners of MAN Insan Cendekia Jambi province is a reference institution of Islamic-based education in Jambi province regarding institutional quality. Specific targets to be achieved by this research are 1). How is the implementation of academic supervision at MAN Insan Cendekia Jambi Province ?. 2). What are the obstacles to the implementation of academic supervision at MAN Insan Cendekia Jambi Province? The research method used is a descriptive qualitative method, which the researcher describes the research findings in narrative and what is. Data collection techniques used are observation techniques, documentation, and interviews. To check the validity of data then the authors do diligence observation, triangulation, member check, audit trail. And to analyze the data then the authors review and reduce data, data unitization, data categorization, and interpretation of data. The results of the research indicate that: 1) Implementation Implementation of academic supervision in MAN Insan Cendekia Jambi Province implemented in the form as follows: a) Supervision based on direct observation of teaching activities in the classroom; b) Supervision with daily work review; c) Supervision with inspection of teaching equipment; d) Supervision with academic dialogue; e) Supervision through questionnaires. and 2). Obstacles implementation of academic supervision in MAN Insan Cendekia Jambi Province is the number of duties and other responsibilities of the head of the madrasah. Based on the results of research can be concluded that the implementation of academic supervision in MAN Insan Cendekia Jambi Province has been implemented well to produce teacher performance is also good. Keywords: Implementation, Supervision, Academic. Abstrak Penelitian ini bertujuan untuk mengetahui kondisi implementasi supervisi akademik pada MAN Insan Cendekia provinsi Jambi. Dimana kebaradaan MAN Insan Cendekia provinsi Jambi merupakan rujukan lembaga pendidikan berbasis agama Islam di provinsi Jambi dalam hal kualitas kelembagaannya. Target khusus yang ingin dicapai dari penelitian ini adalah: 1). Bagaimana implementasi supervisi akademik di MAN Insan Cendekia Provinsi Jambi?. 2). Apa saja kendala implementasi supervisi akademik di MAN Insan Cendekia Provinsi Jambi? Metode penelitian yang digunakan adalah metode kualitatif deskriptif, yang mana peneliti menguraikan temuan penelitian secara naratif dan apa adanya. Teknik pengumpulan data yang digunakan adalah teknik obervasi, dokumentasi, dan wawancara. Untuk mengecek validitas data maka penulis melakukan ketekunan pengamatan, triangulasi, member check, audit trail. Dan untuk menganalisis data maka penulis melakukan penelaahan dan reduksi data, unitisasi data, kategorisasi data, dan interpretasi data. Hasil penelitian menunjukkan bahwa: 1) Implementasi Implementasi supervisi akademik di MAN Insan Cendekia Provinsi Jambi dilaksanakan dalam bentuk sebagai berikut: a) Supervisi berdasarkan pengamatan langsung kegiatan mengajar di kelas; b) Supervisi dengan peninjauan kerja harian; c) Supervisi dengan pemeriksaan perlengkapan mengajar; d) Supervisi dengan dialog akademis; e) Supervisi melalui pengisian angket. dan 2). Kendala implementasi supervisi akademik di MAN Insan Cendekia Provinsi Jambi adalah Banyaknya tugas dan tanggung jawab lain dari kepala madrasah. Berdasarkan hasil penlitian tersebut dapat disimpulkan bahwa implementasi supervisi akademik di MAN Insan Cendekia Provinsi Jambi telah terlaksana dengan baik sehingga menghasilkan kinerja guru yang juga baik. Kata Kunci: Implementasi, Supervisi, Akademik.